HUBUNGAN ANALISIS UPAH DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI INDOMARET MOJOPAHIT SURABAYA PERSPEKTIF EKONOMI ISLAM - Indri Paramithasari (Journal MISSY (Management and Business Strategy), 2023)
This study aims first, to determine the significant effect of wages on employee work productivity at Indomaret Mojopahit Surabaya Islamic Economic Perspective. Second, to determine the significant effect of work discipline on work productivity of Indomaret Mojopahit Surabaya employees from an Islamic Economic Perspective. Third, to determine the significant effect of wages and work discipline on work productivity of Indomaret Mojopahit Surabaya employees from an Islamic Economic Perspective. This research uses a quantitative approach with the type of associative research. Sampling with non-probability sampling technique. The sampling method uses a saturated sample. The source of the data used in this study is primary data obtained from the distribution of the questionnaire to all employees at Indomaret Mojopahit Surabaya. This study uses the classical assumption test analysis method, multiple linear regression test, hypothesis testing and coefficient of determination test. The results of this study indicate that first there is a significant influence between wages on the work productivity of Indomaret Mojopahit Surabaya employees, as the results of the t test (3.892) > t table (2.034) with a significant result of 0.000 smaller than 0.05. Second, there is a significant influence between work discipline on the work productivity of Indomaret Mojopahit Surabaya employees, as the results of the t test (2.787) > t table (2.034) with a significant result of 0.0009 smaller than 0.05. Third, there is a significant influence between wages and work discipline on the work productivity of Indomaret Mojopahit Surabaya employees. As the results of the F count test (147.102) > F table (3.285) with a significant result of 0.000 less than 0.05. Wages and work discipline have a significant level of influence on the work productivity of Indomaret Mojopahit Surabaya employees. As the result of R Square between wages and work discipline on productivity is 64.3%, meaning that more than 35.7% is influenced by other variables such as: motivation, education, skills, work ethic, nutrition and health, income level.